FRUIT PEEL ECOENZYMES AND BIOSAKA AS EFFICIENT AND EFFECTIVE NUTRIENTS IN ORNAMENTAL PLANTS USING AQUEOUS MEDIA - Rosidah, Eva Hana; Fairuzia, Fazat; Putri, Cindy Elisa; Yuliani, Farida; Mahfudloh, Zumi; Farhanah, Maulina (Agrofarm: Jurnal Agroteknologi, 2025)
Air pollution from toxic exhaust gases from various human activities, such as the remains of motor vehicles, factories, and even gas released by organic waste, is dangerous for human health, especially the lungs. To minimise the impact of air pollution, ornamental plants such as Epipremnum aureum with efficient care and water media are considered, especially for urban areas. Nutrition is the main factor in plant growth, so striving for safe organic nutrients is necessary. The ecoenzymes and biosaka effectively promote plant growth and are safe for human health. The research was carried out with a complete randomised block experimental design with one factor, the type of nutrient solution, consisting of three levels: control in the form of water, ecoenzyme solution 1 mL L-1 water, and biosaka solution 1.5 mL L-1 water, with six replications. The research showed that the highest results were significant in the number of shoots, shoot length, and root number of Epipremnum aureum were influenced by the biosaka solution, followed by the ecoenzyme solution and the control, respectively. Adding biosaka and ecoenzyme solutions can become an efficient and effective source of nutrients in the planting medium, and using water will minimise air pollution.